2021
DOI: 10.2147/jhc.s298538
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 Immunotherapy Improves the Efficacy of Hepatic Artery Infusion Chemotherapy in Advanced Hepatocellular Carcinoma

Abstract: Background Hepatic artery infusion chemotherapy (HAIC) and anti-programmed cell death protein-1 (PD-1) immunotherapy have shown promising outcomes in patients with advanced hepatocellular carcinoma (HCC), respectively. However, the combination of the two treatments has not been reported. In this study, we compared the efficacy of HAIC combined with anti-PD-1 immunotherapy (HAICAP) and HAIC in patients with advanced HCC. Methods Between November 2018 and December 2019, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Numerous clinical trials in patients with uHCC have shown that combination of TKIs and ICIs achieved substantial clinical efficacy, with higher ORR and better survival outcomes than monotherapy. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] In 2020, the FDA approved the combination therapy of atezolizumab plus bevacizumab as a first-line treatment for advanced HCC based on the results of the IMbrave150 trial, which demonstrated an ORR of 33.2% (mRECIST) and median PFS of 6.8 months. 19 The combination therapy of LEN and pembrolizumab showed good anti-tumor activity, with an impressive ORR of 46%, median PFS of 9.3 months, and median OS of 22 months (NCT03006926).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous clinical trials in patients with uHCC have shown that combination of TKIs and ICIs achieved substantial clinical efficacy, with higher ORR and better survival outcomes than monotherapy. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] In 2020, the FDA approved the combination therapy of atezolizumab plus bevacizumab as a first-line treatment for advanced HCC based on the results of the IMbrave150 trial, which demonstrated an ORR of 33.2% (mRECIST) and median PFS of 6.8 months. 19 The combination therapy of LEN and pembrolizumab showed good anti-tumor activity, with an impressive ORR of 46%, median PFS of 9.3 months, and median OS of 22 months (NCT03006926).…”
Section: Discussionmentioning
confidence: 99%
“…20 The ORR of dual therapy in uHCC ranged from 13.6% to 46%. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] TACE is the only guideline-recommended therapy for intermediate HCC patients and showed a high tumor response to uHCC with a tolerable safety profile. Combined therapy with different mechanisms of action may improve outcomes, 34 thus we assessed the triple therapy (LEN+PD-1+TACE) in uHCC, which achieved the highest ORR, conversion rate to liver resection, and pathological CR rate to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the combination of PD-1 antibody and targeted drugs can significantly improve the survival of HCC patients, and the A + T regimen has been one of the first-line treatments for advanced HCC patients [ 8 ]. Jie et al has found that PD-1 antibody plus locoregional therapy can improve the efficiency of anti-PD-1 immunotherapy [ 35 ]. Besides, anti-PD-1 therapy combined with targeted drugs and locoregional therapy can further prolong the survival of HCC patients compared with lenvatinib monotherapy [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…31,34 The combination of HAIC with RT has also been reported to significantly prolong OS and PFS better as compared to sorafenib alone among HCC with VP4 PVTT (median, 9.9 versus 5.3, and 3.9 versus 1.9 months). 121 Recently combining HAIC with TACE and Sorafenib proved to be a safe and better treatment option for patients with PVTT, 122 while addition of anti-PD-1 immunotherapy was reported to improve the efficacy of HAIC in advanced HCC 123 (Table 3).…”
Section: Hepatic Arterial Infusion Chemotherapy (Haic)mentioning
confidence: 99%